(untitled) (Studia Prawnicze / The Legal Studies, 1981)
Legal regulation of abortion in the U.S. shows substantial differences when compared with similar regulation in European countries, even Great Britain. Init¬ially, a historical development of this regulation in the U.S. was similar with the evolution of English law. This similarity was first of all evident in the reception of the Common Law principle of unpunishability of abortion in its first stage, that is up to the moment in which the movements of fetus are felt by woman. Secondly through simoultanious introduction, in the IXth century, of a general prohibition of abortion and than concurrent efforts undertaken in the 60’s of the XXth century aiming towards the liberasation of abortion’s regulation. The model criminal-law code of the American Institute of Law, which has been a prototype of legislation in 13 states, was similar to the Great Britain’s law of 1967, in res¬pect of condition under which an abortion is allowed. However, these regulations differed substantially (if the scope of allowed abortions in concerned). It may be therefore assumed that the process of legalization of abortion in the U.S. was continued in a different manner than the English regulation. In 1970, the four states introduced abortion on woman’s demand. Through its decision of 23.01. 1973 the Supreme Court of the U.S. has recognized the states’ legislation prohibiting abortion up to the moment when the fetus has reached the ability to live outside mother’s organism as unconstitutional. This decision interpreting the Constitution of the ’U.S. with the respect of right to privacy and situation of fetus as an object of legal protection, has also settled an issue which up to this moment was reserved for exclusive competence of state legislation. The judgement of the Supreme Court has been accepted by the majority of American society but at the same time it has activated the opponents of the wide legalization of abortion. This group has been undertaken legal and practical actions aiming at limitation of the scope of allowed abortions. It seems through that the chances of abolishing of this consti¬tutional regulation are minimal.